Lactic Acid Bacterial Supplementation Ameliorated the Lipopolysaccharide-Induced Gut Inflammation and Dysbiosis in Mice - Bhatia, Ruchika; Sharma, Shikha; Bhadada, Sanjay Kumar; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran (Frontiers in Microbiology, 2022)
Lipopolysaccharide (LPS), a gut-transmitted endotoxin from Gram-negative bacteria causes inflammatory diseases leading to the loss of gut barrier integrity and has been identified as a major pathogenic stimulator in many dysfunctions. Hence, supplementation with probiotics is believed to be one of the most effective strategies for treating many inflammatory gut disorders. Although probiotics are known to have a variety of therapeutic characteristics and to play a beneficial role in host defense responses, but the molecular mechanisms by which they achieve these beneficial effects are unknown due to species and strain-specific behaviour. Therefore, in this study, the protective role of five indigenous Lactic acid bacterial strains in ameliorating LPS- induced gut barrier impairment in the C57BL/6 mice model was elucidated. Lacticaseibacillus rhamnosus LAB3, Levilactobacillus brevis LAB20 and Lactiplantibacillus plantarum LAB31 were isolated from infant feces, Pediococcus acidilactici LAB8 from fermented food (Bekang) and Lactiplantibacillus plantarum LAB39 from beetroot. Intraperitoneal injection of LPS (10 mg/kg of body weight) increased the levels of lipocalin, serum markers TNF-α, IL-6, IL-1β and overall disease activity index in the treated group. Furthermore, gene expression of NF-kB, IL-12, Cox-2; mucin-producing genes Muc-2 and Muc-4 and intestinal alkaline phosphatase (IAP) were deleteriously altered in the ileum of LPS treated mice. Furthermore, LPS also induced dysbiosis in gut microbiota where higher abundances of Klebsiella, Enterobacter and Salmonella and decreased abundances of Lactobacillus, Biﬁdobacteria, Roseburia and Akkermansia were observed. Western blotting results also suggested that LPS treatment causes the loss of gut barrier integrity relative to the pre-supplementation with LAB strains that enhances the expression of tight junction proteins and ameliorated the LPS-induced changes and inflammation. Taken together, the overall study suggested that LAB3 and LAB39 were more potent in ameliorating the LPS-induced gut inflammation and dysbiosis.